Phosphorus–iron interaction in sediments : can an electrode minimize phosphorus release from sediments? - Martins, Gilberto (2014)
All restoration strategies to mitigate eutrophication depend on the success of phosphorus (P) removal from the water body. Therefore, the inputs from the watershed and from the enriched sediments, that were the sink of most P that has been discharged in the water body, should be controlled. In sediments, iron (hydr)oxides minerals are potent repositories of P and the release of P into the water column may occur upon dissolution of the iron (hydr)oxides mediated by iron reducing bacteria. Several species of these bacteria are also known as electroactive microorganisms and have been recently identified in lake sediments. This capacity of bacteria to transfer electrons to electrodes, producing electricity from the oxidation of organic matter, might play a role on P release in sediments. In the present work it is discussed the relationship between phosphorus and iron cycling as well as the application of an electrode to work as external electron acceptor in sediments, in order to prevent metal bound P dissolution under anoxic conditions.